Nitric Oxide Enters Quorum Sensing via the H-NOX Signaling Pathway in Vibrio parahaemolyticus - Ueno, Takahiro; Fischer, Jonathan T.; Boon, Elizabeth M. (Frontiers in Microbiology, 2019)
Nitric oxide (NO) plays a major role in the regulation of mammalian biological functions. In recent years, NO has also been implicated in bacterial life cycles, including in the regulation of biofilm formation and the metabolism of the bacterial second messenger signaling molecule cyclic-di-GMP. In a previous study, we reported the discovery of an NO-responsive quorum sensing (QS) circuit in Vibrio harveyi. Here, we characterize the homologous QS pathway in Vibrio parahaemolyticus. Spectroscopic analysis shows V. parahaemolyticus H-NOX is an NO sensory protein that binds NO in 5/6-coordinated mixed manner. Further, we demonstrate that through ligation to H-NOX, NO inhibits the autophosphorylation activity of an H-NOX-associated histidine kinase (HqsK; H-NOX-associated quorum sensing kinase) that transfers phosphate to the Hpt (histidine-containing phosphotransfer protein) protein LuxU. Indeed, among the three Hpt proteins encoded by V. parahaemolyticus, HqsK transfers phosphate only to the QS-associated phosphotransfer protein LuxU. Finally, we show that NO promotes transcription of the master quorum sensing regulatory gene opaR at low cell density.